SYNTHESIS AND PERFORMANCE OF 1-PHENYL-3-METHYL-4-BENZOYL-5-PYRAZOLONE (HPMBP) ON THE EXTRACTION OF CE3+,LA3+, AND GD3+ BY SOLVENT IMPREGNATED RESIN (SIR) METHOD - Rohiman, Asep
The pyrazolone and their derivates compound has been known that can be used for the selective extraction and separations of metal ions such as rare earth ions. In the experiment, HPMBP has been synthesized by jensen methode for extraction of rare earth ions by solvent impregnated resin method. The HPMBP result is yellow colours powder. Characterisation of compound was established by melting point, IR and NMR spectral data. Then, HPMBP impregnated resin was prepare by adsorption of chelating ligand onto macroporous, Amberlite XAD-16. The maximum amount of HPMBP that can be immobile towards XAD-16 achieved at weight ratio HPMBP and Amberlite XAD-16 is 3 : 2. Futhermore , SIR was produced at that ratio used to the extraction of Ce3+,La3+, and Gd3+ in the HNO3 0.1 M medium as aquous phase by batch way. The best condition of pH to the extraction Ce3+,La3+, and Gd3 achieved at pH = 3.1 ; pH = 2.19 and pH = 1.70 , respectively. The development of research in pyrazolone derivative is important for syntetic sample, and to enrichment method in separation and purification rare earth metal ions